AB0528 CHARACTERIZATION OF ANTI-MPO POSITIVE INTERSTITIAL LUNG DISEASE. CLINICAL-SEROLOGIC AND RADIOLOGIC FEATURES AND SURVIVAL. (2nd June 2020) - Cassone, G.; Dei, G.; Sambataro, G.; Manfredi, A.; Cerri, S.; Vacchi, C.; Faverio, P.; Sambataro, D.; Gozzi, F.; Vancheri, C.; Salvarani, C.; Luppi, F.; et al.
Abstract : Background: Prevalence of anti-neutrophil cytoplasmic antibody (ANCA) in patient with idiopathic pulmonary fibrosis (IPF) ranges from 1 to 35%, mainly anti-MPO. The presence of ANCA positivity seems to be a poorer prognostic factor in patient with IPF, and some of these patients will develop clinical vasculitis (7-23%). Unfortunately, the majority of the available studies on this topic are retrospective and the real natural history of the disease remains poorly understood. Objectives: Aim of the study was to investigate the clinical, serological and radiologic features of patients with interstitial lung disease (ILD) and positivity for anti-MPO, and to evaluate the survival of this population compared with IPF patients. Methods: We retrospectively analysed 30 patients with ILD and anti-MPO antibodies, without diagnosis of vasculitis, from 3 different rheumatology-pulmonology Italian Center. For each patient, clinical, radiologic and serological data were evaluated. Treatments were also collected, both immunosuppressants or antifibrotic agents. Finally, survival of ILD-MPO patients and of 90 unselected idiopathic pulmonary fibrosis (IPF) patients was compared. Results: Thirty patients were enrolled in the study (see table for the characteristics of the patients). Fibrosing pneumonia was described in 73.3% of patients (usual interstitial pneumonia [UIP] in 19 patients), and 10 patients (33.3%) received antifibrotic drugs, all with UIP pattern. Of interest, 7 patients were treated with immunosuppressants (azathioprine, cyclophosphamide, mycophenolate mofetil), independently by the ILD pattern and 21 (70%) low dosage of steroids. After a median period of 23.5 months (range 11-111), 7 patients developed an ANCA associated vasculitis, while other 3 developed other rheumatic diseases. Finally, when compared with IPF, ILD-MPO patients had a better survival (81.2%±0.9 vs 54.7±0.7 for ILD-MPO and IPF, respectively; p=0.045) Conclusion: ILD positive for anti-MPO antibodies are still a not definite condition. We need larger population to identify possible markers for the evolution in an ANCA associated vasculitis, to define the prognosis of disease and the better therapeutic approach. References: [1]Mohammad AJ, et al. Pulmonary Involvement in Antineutrophil Cytoplasmic Antibodies (ANCA)-associated Vasculitis: The Influence of ANCA Subtype. J Rheumatol. 2017;44:1458-67 Disclosure of Interests: None declared